2019
DOI: 10.31436/iiumej.v20i2.1119
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Finite Element Analysis of Solvent Cast Poly(lactic Acid) Thin Film Blends

Abstract: A combined experimental and finite element analysis () investigation was performed to study the effect of incorporating poly(propylene carbonate)(PPC) and curcumin on the mechanical properties of poly(lactic acid) (PLA). In addition, the chemical interaction and morphological changes brought upon by each subsequent additive were also observed. The addition of PPC at 30 wt% into PLA causes a decrease in strength and modulus by 51% and 68% respectively whilst inducing higher elongation by 74%.  The resultant dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…PPC is a biodegradable polymer derived from CO 2 and propylene oxide, and its ester units exhibit high chain flexibility and good flow properties . Recently, the PLA/PPC blends were prepared by casting method using chloroform, a hazardous solvent. Although this technique is convenient for laboratory-scale prototyping with low production volumes, it is not widely applicable at the industrial level . Moreover, the use of chloroform in food packages, drugs, and cosmetics is strictly banned by The Food and Drug Administration because of evidence indicating it may cause cancer .…”
Section: Introductionmentioning
confidence: 99%
“…PPC is a biodegradable polymer derived from CO 2 and propylene oxide, and its ester units exhibit high chain flexibility and good flow properties . Recently, the PLA/PPC blends were prepared by casting method using chloroform, a hazardous solvent. Although this technique is convenient for laboratory-scale prototyping with low production volumes, it is not widely applicable at the industrial level . Moreover, the use of chloroform in food packages, drugs, and cosmetics is strictly banned by The Food and Drug Administration because of evidence indicating it may cause cancer .…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, with a rise in PPC up to 75%, PLA sphere particles precipitate within the PPC matrix (Figure 7D). The physicomechanical test results revealed that PPC 30–40 wt% was the optimum amount in PLA 123‐125 …”
Section: Biodegradable Pla/polymermentioning
confidence: 99%
“…The physicomechanical test results revealed that PPC 30-40 wt% was the optimum amount in PLA. [123][124][125] Furthermore, after blending compatibilizers such as curcumin (Cur) 1 wt%, functionalized polyolefin elastomers (POE-g-GMA) range between 3-5 wt%, nano SiO 2 -g-PLA/PPC (2 wt%), multiwalled carbon nanotubes (MWCNTs) 3 wt% and graphene oxide nanoparticle of 0.5 wt% with 2 wt% PEG enhances the interfacial adhesion between PLA and PPC. [126][127][128] Similarly, the maleic acid (5 wt%) with transesterification catalyst tetra-butyl titanate (TBT) of 1-2 wt%, PLA-b-PPC block copolymers with TBT 1 wt%, polyethylene glycol-polyhedral oligomeric silsesquioxane (PEG-POSS) of 4 wt% and mica (3 wt%) resulting in better mechanical properties.…”
Section: Poly(propylene Carbonate) Ppcmentioning
confidence: 99%
“…4 were the features of C=O in PLA. PLA contains C=O groups because it was derived from lactic acid, which has a high carbon chain (Shaharuddin et al 2019). However, the findings of Naayi et al (2018) contradicted that interpretation, defining the adsorption peak between 430 cm -1 and 781 cm -1 as the Al-O stretching vibration band in alumina.…”
Section: Infrared Spectral Propertiesmentioning
confidence: 99%